Service-Oriented Computing : 13th International Conference, ICSOC 2015, Goa, India, November 16-19, 2015, Proceedings - Barros, Alistair; Grigori, Daniela; Narendra, Nanjangud C.; Dam, Hoa Khanh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the proceedings of the 13th International Conference on Service-Oriented Computing, ICSOC 2015, held in Goa, India, in November 2015. The 23 full, 9 short, and 5 demo track papers presented in this volume were carefully reviewed and selected from 132 submissions. The research track papers are organized in topical sections named: internet of services/things; data services and cloud platform management; cloud services management; service composition; business process management; cloud services; QoS and trust; service composition. .
Keywords: Software engineering; Computer Communication Networks; Information storage and retrieva; Information Systems; Information technology; Software Engineering; Computer Communication Networks; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Management of Computing and Information Systems; IT in Business